Islam Puritan VS Islam Moderat (Menapak Gagasan Khaled Abou el Fadl dalam The Great Thefl: Wrestling Islam from Extremists) - Mun’im, A. Rafiq Zainul (Universitas Nurul Jadid, 2018)
This article aims to examine puritan Islam vs moderate Islam by review the idea of Khaled Abou el Fadl in his scientific work entitled The Great Thefl: Wrestling Islam from Extremists. The results, that puritan Islam was a religious movement that existed since the days of Wahhabism in the 18 M and reached its peak in the 20 M. They were a Muslim minority who always spoke out calling for propaganda and absolutism and no compromise. Responding to this phenomenon, moderate Islam is required to take part in addressing puritanical Islam. Some of the offers presented were defensive jihad, being aggressive and also loudly voicing peace.